2017
DOI: 10.1007/s00606-017-1390-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization in the genus Passiflora L.: an approach to understanding its complex variability

Abstract: The International Center for Tropical Agriculture (CIAT) believes that open access contributes to its mission of reducing hunger and poverty, and improving human nutrition in the tropics through research aimed at increasing the eco-efficiency of agriculture. CIAT is committed to creating and sharing knowledge and information openly and globally. We do this through collaborative research as well as through the open sharing of our data, tools, and publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 43 publications
4
27
0
Order By: Relevance
“…We checked that these articles included field observations or anecdotal records of plants being visited by the sword-billed hummingbird (Table 1). Following this procedure, in addition to personal field observations, and study reports of the interaction [22–24,26,3034], we compiled 24 plant species as the “plant guild” of E . ensifera (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…We checked that these articles included field observations or anecdotal records of plants being visited by the sword-billed hummingbird (Table 1). Following this procedure, in addition to personal field observations, and study reports of the interaction [22–24,26,3034], we compiled 24 plant species as the “plant guild” of E . ensifera (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The pattern of clustering based on the pollinic characteristics allowed to classify the species into two subgenera, Passiflora and Decaloba, congruent with the classification of Feuillet and MacDougal (2003) and supported by phylogenetic studies using molecular markers and sequencing technique (Yockteng and Nadot 2004, Hansen et al 2006, Mäder et al 2010, Porter-Utley 2014, Milwardde-Azevedo et al 2014b, Muschner et al 2012, Krosnick et al 2013, Ocampo and D'Eeckenbrugge 2017. These authors revealed that the Passiflora and Decaloba subgenera showed monophyletic clades.…”
Section: Discussionmentioning
confidence: 57%
“…Principal Components Analysis (PCA) is a useful statistical method to evaluate morphological variation. It has been used to circumscribe taxa of plants from the Bromeliaceae (Gardner, 1983), Passifloraceae (Porter-Utley, 2003Ocampo Pérez, 2007;Ocampo Pérez & Coppens d'Eeckenbrugge, 2017), Fabaceae (Castro et al, 2005), Arecaceae (Henderson, 2004(Henderson, , 2006, and the Calceolariaceae (Puppo, 2008), among others. The data used in the PCA were the mean values of measurements taken from each specimen.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%